The contribution of cognitive control and perceptions of risk to problematic driving among young adults - O'Brien, Fearghal (Trinity College (Dublin, Ireland). School of Psychology, 2013)
Every year, millions of drivers throughout the world lose their lives in traffic incidents and young drivers make up a disproportionate number of those killed on the road. There has been no shortage of explanations for these high rates though an increasingly popular explanation points to the underdeveloped brains of young people which lead them to engage in greater risks.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin.